A longitudinal examination of the interplay between personality vulnerability and need‐based experiences in adolescents' depressive symptoms. Issue 6 (25th June 2020) - Vandenkerckhove, Beatrijs; Vansteenkiste, Maarten; Brenning, Katrijn; Boncquet, Michiel; Flamant, Nele; Luyten, Patrick; Soenens, Bart
Abstract: Objective: This study aimed to examine the interplay between the personality vulnerability dimensions of self‐criticism and dependency and experienced satisfaction or frustration of the basic psychological needs in relation to adolescents' depressive symptoms. In doing so, we investigated both indirect associations between personality and depressive symptoms (through need‐based experiences) and interactions between personality and need‐based experiences (i.e., moderation). Method: A total of 149 adolescents (52% female, Mag e  = 15.20 years at initial assessment, SD  = 3.09) participated in this three‐wave longitudinal study with 6‐month intervals. At each wave, adolescents reported on their personality, need‐based experiences, and depressive symptoms. Results: Multilevel analyses showed that dependency and self‐criticism related to experiences of need frustration and depressive symptoms at both the between‐person level (i.e., the level of interindividual differences) and the within‐person level (i.e., the level of intraindividual change). In turn, need frustration was related to adolescents' depressive symptoms at both levels of analysis. Personality did not significantly moderate the associations between the psychological needs and depressive symptoms. Conclusion: The results suggest that self‐criticism and dependency are related to experiences of psychological need frustration and depressive symptoms at the level of both interindividual differences and within person‐change.